DAMPAK PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG DALAM PENGGUNAAN DOSIS ABU CANGKANG KELAPA SAWIT DAN DOLOMIT - Hutauruk, Sixtus; Sipayung, Patricius; Harefa, Kurnia Selekta Etika (LPPM Universitas Katolik Santo Thomas Medan, 2023)
This research aims to determine the effect of doses of oil palm shell ash and dolomite on the growth and production of maize plants. This study used a factorial randomized block design consisting of two factors. The first factor is the dose of palm shell ash (A) which consists of four levels, namely: (A0) = 0 g (0 tons/ha), (A1) = 30 g/polybag (6 tons/ha), (A2) = 60 g/polybag (12 tonnes/ha) and (A2) = 90 g/polybag (18 tonnes/ha). The second factor was dolomite (D) dosing which consisted of three levels: (D0) = 0 g (0 tons/ha), (D1) = 15 g/polybag (3 tons/ha) and (D2) = 30 g /polybag (6 tonnes/ha). Parameters observed were plant height, number of leaves, stem diameter, leaf area, cob length without cob, cob diameter without cob, cob weight with husk, cob weight without cob and straw weight. The effect of the dose of oil palm shell ash depends on the dose of dolomite which is shown in the diameter of the cobs without husks, in treatment D0 the dose of palm ashes 78.07 g/polybag resulted in a maximum cob diameter without husks of 3.95 cm, treatment D1 increased linearly, treatment D2 the dose of palm shell ash 85.03 g/polybag resulted in a maximum diameter of cobs without husk of 3.98 cm. The largest straw weight was 311.30 g with a dose of shell ash of 56.93 g/polybag.